Unwillingness to participate in health checks for cardiometabolic diseases: A survey among primary health care patients in five European countries - de Waard, Anne-Karien M; Korevaar, Joke C; Hollander, Monika; Nielen, Mark M J; Seifert, Bohumil; Carlsson, Axel C; Lionis, Christos; Søndergaard, Jens; Schellevis, François G; de Wit, Niek J; SPIMEU project group (Health science reports, 2021)
BACKGROUND AND AIMS: Since cardiometabolic diseases (CMD) are a frequent cause of death worldwide, preventive strategies are needed. Recruiting adults for a health check could facilitate the identification of individuals at risk for CMD. For successful results, participation is crucial. We aimed to identify factors related to unwillingness to participate in CMD health checks. METHODS: We performed a cross-sectional study in the Czech Republic, Denmark, Greece, the Netherlands, and Sweden. A questionnaire was distributed among persons without known CMD consulting general practice between January and July 2017 within the framework of the SPIMEU study. RESULTS: In total, 1354 persons responded. Nine percent was unwilling to participate in a CMD health check. Male gender, smoking, higher self-rated health, never been invited before, and not willing to pay were related to unwillingness to participate. The most mentioned reason for unwillingness to participate was "I think that I am healthy" (57%). Among the respondents who were willing to participate, 94% preferred an invitation by the general practitioner and 66% was willing to pay. CONCLUSION: A minority of the respondents was unwilling to participate in a CMD health check with consistent results within the five countries. This provides a promising starting point to increase participation in CMD health checks in primary care.
Keywords: willingness to participate; cardiovascular disease; health check; cardiometabolic disease; prevention